Estimating the Energy Content of Wastewater Using Combustion Calorimetry and Different Drying Processes - Korth, Benjamin; Maskow, Thomas; Günther, Susanne; Harnisch, Falk (Frontiers in Energy Research, 2017)
The energy content of wastewater is routinely assessed by chemical oxygen demand (COD) measurements that only provide an incomplete picture and the data fundament of other energy parameters remains scarce. The heat of combustion (∆CH) of raw wastewater from a municipal wastewater treatment plant (WWTP) was assessed using oven drying method (∆CH = −6.8±4.3 kJ L−1, n = 20) and freeze drying method (∆CH = −20.2±9.7 kJ L−1, n = 6) illustrating the substantial loss during the oven drying approach. Normalizing ∆CH to COD of raw wastewater yielded −6.2±3.5 kJ gCOD−1 for oven-dried samples (n = 14) and −13.0±1.6 kJ gCOD−1 for freeze-dried samples (n = 3). A subsequent correlation analysis with further chemical wastewater parameters revealed a dependency of ∆CHvol on COD, TOC, C:N ratio and total sulfur content. To verify these correlations, wastewater of a second WWTP was sampled and analyzed. Only COD and TOC were in accordance with the data set from the first WWTP representing potential predictors for the chemical energy stored in wastewater for comparable WWTPs. Unfortunately, during the most practical method (oven drying), a certain loss of volatile compounds is inevitable so that the derived ∆CHvol systematically underestimates the total energetic potential of wastewater. Nevertheless, this work expands the, so far, little data fundament on the energy resource wastewater and implies the requirement for further long-term studies on different sites and different wastewater types with a highly standardized sample treatment protocol.